Respuestas
Respuesta dada por:
8
esa es la respuesta. Espero te sirva.
Adjuntos:
![](https://es-static.z-dn.net/files/d36/7a63ba4fa00cb626a8e00067917cac40.jpg)
Respuesta dada por:
5
Tenemos.
p₁(1,2)
p₂(3,4)
Formula.
Pendiente(m) = (y₂ - y₁)/(x₂ - x₁)
m = (4 - 2)/(3 - 1)
m = 2/2
m = 1
Respuesta.
La pendiente(m) = 1
p₁(1,2)
p₂(3,4)
Formula.
Pendiente(m) = (y₂ - y₁)/(x₂ - x₁)
m = (4 - 2)/(3 - 1)
m = 2/2
m = 1
Respuesta.
La pendiente(m) = 1
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años